Optimizing the Role of Curriculum Management in Integrating Islamic Values in Islamic Educational Institutions - Surahman, Susilo; Nayla, Muthia Rahman (Prodi PAI STIT Sunan Giri Bima, 2025)
One of the crucial issues in education is the need to integrate character values into the learning process. This requires the optimization of curriculum management as a strategic instrument for shaping a school culture rooted in values. The curriculum functions not merely as a formal administrative document but as a value-based framework that guides the overall direction of education. This study aims to describe the role of curriculum management in integrating character values, particularly within the context of Islamic educational institutions at the elementary level. The method used is a literature review with a qualitative approach. The findings indicate that effective curriculum management facilitates collaboration among teachers, principals, and stakeholders in designing learning strategies that embed values such as responsibility, honesty, discipline, and cooperation. The success of value integration strongly depends on the alignment between curriculum planning, implementation, and evaluation. Furthermore, strengthening school culture through value-driven vision and mission, as well as professional teacher development, serves as a key supporting factor. Therefore, curriculum management plays a central role in ensuring that learning is not only academically oriented but also transformative in shaping students' character.